The disclosure of alleged child sexual abuse: an investigation of criminal court transcripts from Scotland - Skinner, Guy C. M. (Psychology, crime & law, 2019)
This study systematically assessed children’s disclosure processes and lawyers’ questioning about children’s disclosures in the courtroom. We analysed transcripts of 72 trials in which 5- to 17-year-old children testified as alleged victims of sexual abuse and found that children typically delayed disclosing abuse for over 6 months, with the length of delay greater when the alleged perpetrator-victim relationships were closer. When questioning children about disclosure, prosecutors used more directive and option-posing questions, and sought to establish the plausibility, credibility, reliability, and consistency of children’s disclosures. On the other hand, defence lawyers used more suggestive questions than prosecutors, and sought to undermine children’s testimony by accusing them of lying or being coached. Children’s responses to questions about their disclosure differed depending on who was questioning them: notably, children contradicted themselves more during cross-examinations than direct-examinations. Both prosecutors and defence lawyers tended to ask developmentally ‘risky’ questions, illustrating the difficulties that may arise when attempting to achieve a balance between securing accurate testimony and protecting the right of defendants to challenge the evidence against them.